2010
DOI: 10.1128/jcm.02417-09
|View full text |Cite
|
Sign up to set email alerts
|

Novel Duplex Real-Time PCR Assay Detects Bordetella holmesii in Specimens from Patients with Pertussis-Like Symptoms in Ontario, Canada

Abstract: Bordetella holmesii is a human pathogen found mainly in immunocompromised patients. A specific real-time PCR assay was developed and successfully used to identify specimens from which B. holmesii was misidentified as Bordetella pertussis and to establish the prevalence of B. holmesii in Ontario patients with pertussis-like symptoms.The Gram-negative bacterium Bordetella holmesii was first described in 1995. It is known to cause disease (e.g., septicemia) in patients with serious underlying medical conditions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 15 publications
1
47
0
9
Order By: Relevance
“…Evaluation of the new assay showed that less than 1% of previously tested pertussis-positive specimens were B. holmesii. 17 Polymerase chain reaction tests were considered positive for pertussis at cycle threshold values of 35 or less, and indeterminate at 36-40. Specimens with no amplification signal were considered negative.…”
Section: Laboratory Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the new assay showed that less than 1% of previously tested pertussis-positive specimens were B. holmesii. 17 Polymerase chain reaction tests were considered positive for pertussis at cycle threshold values of 35 or less, and indeterminate at 36-40. Specimens with no amplification signal were considered negative.…”
Section: Laboratory Datamentioning
confidence: 99%
“…The laboratory methods have been previously described. [15][16][17] Briefly, until May 28, 2012, primers targeting the insertion sequence IS481 were used to detect B. pertussis. Following this date, primers targeting a 50-base pair segment of the recA gene were also included to distinguish B. pertussis from Bordetella holmesii.…”
Section: Laboratory Datamentioning
confidence: 99%
“…Bordetella species have limited genetic diversity, and as such, commercially used PCR assays are often unable to differentiate between Bordetella species. 13,20,179,181,183,184 Furthermore, immunisation against B. pertussis offers little protection against B. holmesii and B. parapertussis, and clinically, infection caused by these species can closely resembles B. pertussis infection. 20 Both B. holmesii and B. parapertussis have been detected in B. pertussis outbreaks and are believed to contribute to pertussis notifications.…”
Section: Future Researchmentioning
confidence: 99%
“…20 Both B. holmesii and B. parapertussis have been detected in B. pertussis outbreaks and are believed to contribute to pertussis notifications. [13][14][15][16][17][18][19][20]103,183 In 2013, only 7% of Australian laboratories reported using multi-target PCR assays that could distinguish between the Bordetella species, with the remaining 93% of Australian laboratories likely to return false positive results for B. pertussis in approximately 90% of cases. 13 As PCR assays are further improved and specialised to detect other species of Bordetella, such as B. holmesii and B. parapertussis, it may be possible to quantify the contribution of these species to pertussis notifications and assessments of vaccine effectiveness.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation